KEPUASAN KERJA TENAGA PENDIDIK DI LEMBAGA PENDIDIKAN ISLAM - Munandar, Aji (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
In general, the purpose of human work is nothing but getting a reward in order to fulfill their needs. However, many of them feel that they are not enough with the rewards they get. From here arises the desire to obtain job satisfaction. Likewise in the world of education, which is called an educational institution, in this case the educators who have obtained salary are still not feeling enough, because their job satisfaction has not been achieved. In this case there are several categories of job satisfaction, among others, namely: pay satisfaction, promotion satisfaction, supervition satisfaction, coworker satisfaction, satisfaction with the work itself, altruism, status and environment. Job satisfaction of education workers is closely related to several variables that are quite influential with the quality of education, such as: performance, organizational commitment, customer satisfaction, absenteeism, turnover, work irregularities and life satisfaction. In other words, when teachers do not get their job satisfaction, adverse impacts will arise which will hamper the process of achieving the goals of the institution.